Carbon fibers/ZnO nanowires hybrid nanogenerator based on an insulating interface barrier. Issue 35 (18th April 2017) - Du, Yunzhe; Fu, Chuankai; Gao, Yunzhi; Liu, Li; Liu, Yawei; Xing, Lixin; Zhao, Feng
Abstract : An insulating layer was used to replace the noble metal to accumulate net charge of a novel design ZnO nanowires nanogenerator. Abstract : Nanogenerators (NGs) based on the piezoelectric property of ZnO nanowires (NWs) have become an important component to harvest mechanical energy from the environment. In one category of ZnO NGs, the high-work function noble metal electrode is applied to deflect ZnO NWs, and electricity is generated due to the Schottky barrier formed between ZnO NWs and the noble metal. Herein, an insulating layer was used to replace the expensive noble metal to accumulate net charge, and a novel NG was composed by carbon fibers (CFs) and ZnO NWs. Because of a relative slip among CFs, ZnO NWs would generate inner potential by bending each other. Due to the combination of an enormous number of ZnO NWs, an electric output of 2 mV and 0.2 nA was generated. Current–voltage curves indicated the entire ohmic contact of the designed NG, while electrochemical impedance spectroscopy demonstrated the existence of an interface barrier. Since a noble metal electrode was avoided in the ZnO NG, the manufacturing cost was reduced and the fabrication process was simplified. This study proposes a novel strategy for designing feasible ZnO NG in extensive applications.